Sacrospinous ligament fixation for prevention and treatment of vaginal vault prolapse: a retrospective study of 45 cases - RK, Ramesh Kumar; Kamat, Leena; T., Shilpa; Andola, Shruthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To assess intraoperative and postoperative complications and to evaluate recurrence of vault prolapse in women who have undergone unilateral (left) Sacrospinous ligament fixation. Methods: Between January 2007 and January 2015, 45 women (mean age 56.5 years, range 35 to 78 years) underwent vaginal unilateral (left) Sacrospinous ligament fixation at Shree Dharmasthala Manjunatheshwara (SDM) College of Medical Sciences, Dharwad, India. 15 patients had prior hysterectomy. Concomitant hysterectomy and Sacrospinous ligament fixation was performed in 30 patients. Sacrospinous ligament fixation was combined with additional procedures like Trans-Obturator tape (TOT) insertion in 2 (4.6%) patients. Results: All patients were analyzed for intraoperative and postoperative complications. 1 patient had Urinary tract infection (n=1, 2.2%), 1 patient had haemorrhage requiring blood transfusion (n=1, 2.2%). The mean follow up was for 15 months (range 6 months to 24 months). 1 patient (2.2%) had asymptomatic recurrent cystocele and 1 patient (2.2%) had dyspareunia. No recurrence of vault prolapse was noted. Conclusions: Sacrospinous ligament fixation is a simple, effective and safe procedure for treatment and prevention of vault prolapse with least complications and recurrence rates.